Bronze Ages of the Muş/Varto Tepeköy Mound - Sabahattin Erdoğan; Mikail Erçek; Yunus Çiftçi; Hanifi Biber; Hakan Yılmaz; Gulan Ayaz (Anadolu Araştırmaları)
The Eastern Anatolia Region has been an important route or an important residence despite being a mountainous region and with its climatic challenges. It has been inhabited continuously since prehistoric times and managed to become the focal point of many great cultures, kingdoms, and states. Specifically, the great migrations thought to have started at the end of the Chalcolithic Age and the subsequent cultures continued to use the region as their homeland. These migration waves, in the Muş Region, have previously been documented by only limited research. Now, more data have been collected with the Tepeköy Mound excavations. Tepeköy is an important mound as it is the first layered mound excavation in the Muş Region. The excavations Medieval, Iron Age and Bronze Age layers where some rich features of the architecture and objects could be seen. It provides data on the Early and Middle Iron (Urartian) periods of the Iron Ages. Mound, which started with the Early Transcaucasian Culture and used continuously until today, provides crucial data for the history of both the Muş Region and the Eastern Anatolia Region. Being a unique center with its stratification, architectural elements and other finds, the mound may answer many questions on the history of the region and transcaucasian migrations.